Interspecific Density Influences the Adaptive Significance of Provisioning Coordination Between Breeding Partners - Burdick, Chloe; Siefferman, Lynn (Frontiers in Ecology and Evolution, 2020)
Cooperation between parents in species with biparental care can reduce sexual conflict and increase reproductive success. If parents cooperate in a conditional way- that is, alternate feeding visits to offspring- this should equalize parental investment and may improve nestling growth. Environmental variation, including competition for limited resources, may influence the need for, and benefits of, parental cooperation. We measured the benefits of partner coordination in offspring provisioning behavior among eastern bluebird partners (Sialia sialis) in which the strength of interspecific density varied spatially. Tree swallows (Tachycineta bicolor) are a recent (<40 years) arrival in our study area, are aggressive nestbox competitors with eastern bluebirds, and their density varies across the field site. Nesting among higher densities of tree swallows led to reduced parental feeding rates and reproductive success of bluebirds. Partner alternation, however, did not vary with tree swallow density. Additionally, alternation level and provisioning rate only influenced nestling growth in areas of high swallow density. It may be that the benefits of parental coordination may only be apparent when environmental conditions are poor. This study provides an important new perspective on the resolution of negotiations between breeding partners; environmental variation could influence the benefits of parental cooperation in a wide variety of animals.